Identification and characterization of the critical genes encoding Cd-induced enhancement of SOD isozymes activities in Zhe-Maidong (Ophiopogon japonicus) - Hou, Ruijun; Wang, Zhihui; Zhu, Qian; Wang, Jie; Zhou, Yifeng; Li, Ye; Liu, Huijun; Zhao, Qian; Huang, Jun (Frontiers in Plant Science, 2024)
Superoxide dismutase (SOD) protects plants from abiotic stress-induced reactive oxygen species (ROS) damage. Here, the effects of cadmium (Cd) exposure on ROS accumulation and SOD isozymes, as well as the identification of significant SOD isozyme genes, were investigated under different Cd stress treatments to Zhe-Maidong (Ophiopogon japonicus). The exposure to Cd stress resulted in a notable elevation in the SOD activity in roots. Cu/ZnSODa and Cu/ZnSODb were the most critical SOD isozymes in response to Cd stress, as indicated by the detection results for SOD isozymes. A total of 22 OjSOD genes were identified and classified into three subgroups, including 10 OjCu/ZnSODs, 6 OjMnSODs, and 6 OjFeSODs, based on the analysis of conserved motif and phylogenetic tree. Cu/ZnSOD-15, Cu/ZnSOD-18, Cu/ZnSOD-20, and Cu/ZnSOD-22 were the main genes that control the increase in SOD activity under Cd stress, as revealed via quantitative PCR and transcriptome analysis. Additionally, under various heavy metal stress (Cu2+, Fe2+, Zn2+, Mn2+), Cu/ZnSOD-15, Cu/ZnSOD-18, and Cu/ZnSOD-22 gene expression were significantly upregulated, indicating that these three genes play a critical part in resisting heavy metal stress. The molecular docking experiments performed on the interaction between oxygen ion (O2•−) and OjSOD protein have revealed that the critical amino acid residues involved in the binding of Cu/ZnSOD-22 to the substrate were Pro135, Ile136, Ile140, and Arg144. Our findings provide a solid foundation for additional functional investigations on the OjSOD genes, as well as suggestions for improving genetic breeding and agricultural management strategies to increase Cd resistance in O. japonicus.